DeLone and McLean Model Analysis of Success Factors of SIDEMANG Application in Palembang City - Faris, Haninda Ammar; Wedhasmara, Ari; Putra, Apriansyah; Kurnia, Rizka Dhini; Bardadi, Ali; Fitri, Shofiyah (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
Indonesia is ranked 77th in the world in electronic-based government systems, especially the City of Plembang is ranked 89th regarding the evaluation of smart city improvement in Indonesia. One of the latest applications used in the past year is the SIDEMANG application, which is an information system that has the use and purpose of facilitating access to administrative services related to personal and agency licensing files online at the village and sub-district levels in Palembang city, but this is also not free from obstacles, especially internet signals. Therefore, an analysis is needed related to the implementation of Information Systems, to assess the success of applications that have been implemented, especially government digital services. DeLone and McLean Information System Success Model is used, to see the significant factors that cause the success of Information System implementation. The data analysis method used in this research is quantitative because the data collected is in the form of numbers and will be analyzed using the SmartPLS application statistical technique, using a sample size of 97 respondents. The results showed that the information quality factor was not significant to the intention or use of the application, the system quality factor was not significant to the intention or use of the application, the system quality factor was not significant to user satisfaction, the service quality factor was not significant to user satisfaction. Recommendations for the Palembang City Communication and Information Office are related to the evaluation and improvement of the SIDEMANG application using the DeLone and McLean Model analysis. In particular, improvements to the quality of information that can influence citizens to use the application, improvements to the quality of the system that can invite and satisfy users in using the application, and improvements to service quality factors on citizen satisfaction.